Assessment on Quality of Coarse and Fine Aggregate of Riverbed Quarry as Construction Material Used in Kaski District of Nepal - Banstola, Ramesh; GC, Santosh; Pandey, Surendra; KC, Abit; Koirala, Sudeep; Bastola, Shirash Kumar (Technical Journal, 2023)
Quality of the composite material and ingredient of the materials in composite material plays a vital role in the sustainable infrastructure development. The quality of concrete is conformance to technical requirements as per specification or fitness for uses having minimum acceptance level to use the products. Among the various properties of fine and coarse aggregate of sampled quarry, only physical and mechanical properties of coarse and fine aggregates were tested in the laboratory, analyzed and compared with IS code and Standard Specification for Road and Bridges Works-2073 (with second amendment-2078) of Department of Roads (DoR), Nepal. Results revealed that physical properties of all the sampled quarry on gradation of coarse and fine aggregate lies within the IS code provision, whereas only source of Rato Pairo Mishi Tunda Shanik Ghat and Gahara Ghat comply the specifications defined by Standard Specification for Road and Bridge Works -2073 (with second amendment-2078), The specific gravity and water absorption of all the sampled quarry satisfied as per the Standard Specifications for Road and Bridge Works-2073 (with second amendment-2078). The mechanical properties such as crushing value of coarse aggregate of all sampled quarry satisfied standard value, impact value of sampled aggregate from Babya Tara, Mahari Ghat and Chuina Pahara Ghat dosen't comply within standard value, and abrasion value of sampled aggregate from Mahari Ghat and Chuina Pahara Pasupati Ghumari Ghat does not meet the standards as defined by the Standard Specifications for Road and Bridge Works-2073 (with second amendment-2078). The properties of fine and coarse aggregate have significant influence on performance, quality and serviceability of concrete mix & finally influence durability of the engineering structures.